High efficiency electron field emission from protruded graphene oxide nanosheets supported on sharp silicon nanowires - Devarapalli, Rami Reddy; Kashid, Ranjit V.; Deshmukh, Ashvini B.; Sharma, Ponchami; Das, Manash R.; More, Mahendra A.; Shelke, Manjusha V. (Journal of Materials Chemistry C, 2013)
Graphene oxide (GO) potentially has applications in vacuum microelectronic devices for realization of field emission displays. Graphene and its derivatives are expected to be efficient field emitters due to their unique electrical properties. However, the flat sheet structure of graphene or GO allows electron field emission only from the edges of graphene and GO nanosheets. In order to extract maximum field emission current density at lower applied voltage from the GO nanosheets, we supported and stretched them on sharp tips of silicon nanowires (SiNWs). Highly efficient and stable field emission with low turn-on field was observed for these SiNW-GO heterostructures. The sharp protrusions created by stretching of the GO nanosheets on SiNWs locally enhance the electric field and thus enhance the field emission characteristics. The dominant use of silicon in electronic devices makes this approach robust for the development of field emission devices using graphene based field emitters.

Highly durable Li-ion battery anode from Fe3O4 nanoparticles embedded in nitrogen-doped porous carbon with improved rate capabilities - Deshmukh, Ashvini B.; Dwivedi, Pravin K.; Nalawade, Archana C.; Qureshi, Mohammed S.; Shelke, Manjusha V. (Journal of Materials Science, 2020)
For next generation, lithium-ion batteries (LIBs) developing high capacity anode materials are crucial with increasing demand of large-scale application. Conversion-type anode materials are promising if stable cycling behavior could be achieved. In this work, a nitrogen-doped porous carbon-Fe3O4(NPC-Fe3O4) nanocomposite is synthesized via a simple and scalable approach. Composite is prepared by pyrolysis of polymer silica hybrid PolyHIPE (high internal phase emulsion) into NPC, and Fe3O4 nanoparticles (NPs) are anchored on its surface via hydrothermal synthesis. As-prepared NPC-Fe3O4 nanocomposite delivers high reversible capacity of around 1001 mAhg(-1)at 0.1 Ag-1 current density and rate capabilities and displays excellent cycling stability as high as 95% capacity retention even after 400 cycles. Superior electrochemical performance of NPC-Fe3O4 is attributed to the hierarchical porous structure and nitrogen doping of carbon which shorten the diffusion path of Li+ and provide ample space to prevent aggregation of Fe3O nanoparticles. [GRAPHICS] .